Kajian Pengembangan Armada Penjagaan Laut Dan Pantai (Sea & Coast Guard) - Malisan, Johny (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Indonesian archipelagic country geographically provides a tremendous endowment. Therefore, sea transportation is important in the nation life and the national economic development. Building and developing of sea transportation service network continues to be encouraged until the optimal level of service for the community has been achieved. Wide service network could be better accomplished whenever supported by a safety and security of shipping system and conducively as possible to avoid maritime pollution. The development of sea and coast guard fleet in supporting safety and security systems at ports and sea waters as well as the prevention of marine pollution to be carried out by developing them fleet that capable to synergize with other relevant agencies. Law on Shipping (No 17/2008) expressed the need for unification of related agencies in order to be able performing its duties and functions to enforce the law in safety and security of shipping. Supporting of its fleet to be one important part for the smooth of those duties and functions as mandated by the shipping law. An analysis to be done accordingly through some variables that are included in several aspects like human resources, facilities, infrastructure, and range of territorial waters. Its result shows that improvement on several variables in each aspect are still needed so that performance of sea and coast guard fleet could be improved and able to provide maximum service while carrying out its duties and functions.Keywords: development of sea and coast guard fleet, ship safety and security.